2018
DOI: 10.1001/jamapediatrics.2017.5634
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prenatal Ultrasonography and Autism Spectrum Disorder

Abstract: The prevalence of autism spectrum disorder (ASD) has been increasing rapidly, with current estimates of 1 in 68 children affected. Simultaneously, use of prenatal ultrasonography has increased substantially, with limited investigation into its safety and effects on brain development. Animal studies have demonstrated that prenatal ultrasonography can adversely affect neuronal migration. OBJECTIVE To quantify prenatal ultrasound exposure by the frequency, timing, duration, and strength of ultrasonographic scans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
1
17
0
2
Order By: Relevance
“…In a current study by Rosman et al [86], 211 children with developmental disorders (including 107 cases of ASD) were compared to a control group of 209 children in relation to prenatal ultrasound examinations. There were no differences with respect to the main parameters including examination frequency, examination time, acoustic output power, operating modes, etc.…”
Section: Autismmentioning
confidence: 97%
“…In a current study by Rosman et al [86], 211 children with developmental disorders (including 107 cases of ASD) were compared to a control group of 209 children in relation to prenatal ultrasound examinations. There were no differences with respect to the main parameters including examination frequency, examination time, acoustic output power, operating modes, etc.…”
Section: Autismmentioning
confidence: 97%
“…One study found a possible association between ultrasound exposure and delayed speech development [28], but this was refuted by a randomized trial [29]. Two recent case-control studies with questionable methodology have tried to establish a link between ultrasound exposure in utero and autism [30,31], this association was not found in a large randomized trial [32]. One epidemiological study supports the association between ultrasound exposure and non-right handedness [33].…”
Section: Safety Implicationsmentioning
confidence: 99%
“…12 Likewise, a recent study suggested possible association between fetal ultrasound exposure and autism spectrum disorder. 13 Even if some ultrasound exposure is safe, we cannot assume that any amount is safe, and it is critical for epidemiological data to be updated for current technology and practices.…”
Section: Health Risks and Benefitsmentioning
confidence: 99%